Analisis Harga Pokok dan Bentuk Pasar Pakan dan Kaitannya dengan Pengembangan Agribisnis Ayam Ras Rakyat - Yusmichad Yusdja; Effendi Pasandaran (Jurnal Agro Ekonomi, 1996)
One of the government central function is to ensure fair distribution of income more than 14 years, the government has tried to keep poultry industry as a source of income for small scale business under the Presidential Decree, No. 50/81 and No. 22/90. Meanwhile, poultry population had increased steadily, but the poultry industry has developed into a large scale business. The objective of this study is to analyze the role of feed factories under the condition that small scale poultry business has found difficult to develop. The empirical data were collected from poultry farms, feed factories, traders of raw material in West Java, East Java and Lampung. The result indicated that there are a trend toward monopolistic and conglomeration practices in feed and poultry industries. Based on these findings of the study, the government should control the poultry industry market mechanism and the role of enterprise permit should be organized.